Congestion Control Reliability and Adaptive Cooperation for Efficient Underwater Sensor Networks - Junaid Ahmed Inam; Sheeraz Ahmed; Najeeb Ullah; Ali Raza; Ata-ur Rehman; Asghar Khattak; Saqib Shahid Rahim (EAI Endorsed Transactions on Scalable Information Systems, 2018)
Underwater wireless sensor networks (UWSNs) are intended to be positioned at the areas that need to be supervised constantly deprived of the human interaction. Consequently, these networks are likely to stay active for a longer duration. Though, sensor nodes in UWSNs are equipped with finite energy resources. Furthermore, congestion is one of the biggest challenges in UWSNs because it leads to data packet loss and ultimately shorten network lifetime. In this paper, a congestion control model in UWSNs with congestion control is considered. A routing protocol is purposed which will be a modification of current UWSNs protocols such as RACE and ARCUN by presenting their attributes with congestion control mechanism. We will deliver some comparisons between the proposed scheme and the existing schemes and prove that this new scheme with congestion control has better performance than the existing ones.